MODERNISM OF VASYL STEFANYK THROUGH THE MAGIC CRYSTAL OF ALLEGORY - Moklytsia, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article tells about the hidden controversy of the issue of belonging Stefanyk to modernism in general and expressionism in particular. It enphasizes the sis on the need to define the place of realistic and naturalistic means of Stefanyk’s image style. The question of the role of allegory in the hierarchy of artistic means of expressionism is put. It considers the allegorical basis of Stefanyk’s prose, which appears as a result of objectification in naturalistic descriptions and portraits of the author’s personal suffering. It proposes an allegorical interpretation of the novella «Vistuny».